Efektivitas Sistem Informasi Akuntansi dalam Sistem Penggajian Pegawai di PT BNI Life Menggunakan Metode Technology Acceptance Model (TAM) - Prabawa, Hikmat (Universitas Pendidikan Indonesia, 2023)
The efforts to achieve company goals, remuneration for employees is needed. This is one way to improve employee performance and productivity. So consistent cost control must be considered by companies with the help of Accounting Information Systems. This study aims to determine the effectiveness of accounting information systems in the employee payroll system and its application based on perceived usefulness using the Technology Acceptance Model (TAM) method. The research was conducted at PT BNI Life, data collection was carried out by distributing questionnaires and interviews with employees. Variable measurement using the TAM method is based on the perceived usefulness aspect of the effectiveness of the Accounting Information System in the payroll system. Data processing was carried out statistically using SPSS with a Simple Linear Regression Test and several other tests. The results showed that the regression equation between the effectiveness of the accounting information system and payroll procedures at BNI Life was Y = 0.346+0.88X1. The test obtained from Fcount = 15.83 and Ftable (df 4; 25) is 2.76. This proves that Fcount Ftable, meaning that the influence of perceived usefulness on the use of Accounting Information Systems affects the effectiveness of payroll procedures getting stronger and more positive. It can be concluded that the effectiveness of the Accounting Information System (HCIS GreatDay) which has been measured using the TAM method based on perceived usefulness significantly and positively influences the employee payroll system.Keywords: Payroll, PT BNI Life, Accounting Information Systems, Technology Acceptance Model (TAM), Perceived Usefulness.